Feed intake as explanation for density related growth differences of common sole Solea solea. Issue 3 (12th December 2011) - Lund, I.; Steenfeldt, S. J.; Herrmann, B.; Pedersen, P. B.
Abstract Growth of common sole Solea solea is negatively correlated to density, which affects productivity in culture and hence commercial success. Studies of individual feed intake were performed to examine growth and population dynamics at different densities. Three initial stocking densities: 1.0, 2.1 and 3.9 kg m−2 of individually tagged sole, referred to as low density (LD), medium density and high density HD), were examined during 145 days. Despite that tank productivity (g m−2 day−1), was highest for the HD group, the specific growth rate (SGR) decreased significantly with increase in stocking density. Individual size variation was similar between densities, indicating that growth was not associated with hierarchy and dominant behaviour. Individual data indicated that increased density reduced the growth potential of all individuals in a population. Individual feed intake was positively correlated to both fish size and individual SGR. Feed conversion ratio was likewise positively correlated to feed intake. The relative feed intake (g feed g fish−1) was not correlated to fish size at any density tested, but was significantly highest for the LD population. This explains a substantial part of the better growth in the LD group supported by indications of better utilization of the ingested feed.